Exploring Aesthetic Preferences in Rural Landscapes and the Relationship with Spatial Pattern Indices - Massoni, Emma Soy; Varga, Diego; Sáez, Marc; Pintó, Josep (Journal of Landscape Ecology (Berlin, Germany), 2016)
This study examines how local population, tourists and farmers relate to rural landscapes, by exploring visual landscape preferences and the influence of everyday landscapes on the research subjects. Results point towards an immense variability in visual landscape preferences amongst user groups living in or visiting the study area (Plana de l’Empordà, Girona, Spain). Tourists rate grasslands at the top of their preference list, local residents prefer orchards, and farmers favour fields of irrigated herbaceous crops; showing, altogether, that the user's relationship with the landscape determines their visual preferences. Results show that farmers prefer agriculture dominated scenes while local residents and tourists prefer scenes with equilibrium between agricultural and natural elements. Likewise, the presence of margins is widely appreciated aesthetically by all respondents. Furthermore, results underline the importance of landscapes that are familiar to the respondents.